Effect of Formic Acid on In Vitro Ruminal Fermentation and Methane Emission - Kanber Kara; Eray Aktuğ; Alper Çağrı; Berrin Kocaoğlu Güçlü; Erol Baytok (Turkish Journal of Agriculture: Food Science and Technology)
In this study, it was aimed to investigate the effects of formic acid on the in vitro methane production and in vitro ruminal fermentation of alfalfa hay. Effect of 0.0 (control group: YF0), 0.1, 0.2, 0.3, 0.4 and 0.5 ml/L (experimental groups: YF1, YF2, YF3, YF4, and YF5 respectively) formic acid (Amasil85-liquid) addition to rumen fluid on ruminal fermentation parameters of alfalfa hay were determined by using in vitro gas production techniques. Methane production of in vitro incubation increased (to about 20%) with addition of linearly increased formic acid. Linearly increased levels of formic acid addition to rumen fluid has significantly changed the production of in vitro total gas production, metabolic energy (ME) and organic matter digestibility (OMD) at linear, quadratic and cubic. The addition of 0.1 ml/L and 0.2 ml/L formic acid to rumen fluid significantly decreased in vitro total gas production, ME and OMD however addition of 0.3 ml/L and 0.4 ml/L formic acid was not changed in vitro gas production, ME and OMD levels and 0.5 ml/L formic acid was significantly increased all these parameters. Ruminal pH was not changed by addition of formic acid. Formic acid is a safe feed additive because of its properties antibacterial and flavorings and also is used as a fermentation promoter in silage. In this study it has been observed that all doses of formic acid increased in vitro enteric methane production and low doses decreased in vitro total gas production, ME and OMD and high doses have increased all these parameters. High doses have a positive effect on ME and OMD; however formic acid should be used at limited levels in diets due to the negative effect of increasing greenhouse gases. The effect of formic acid addition to the feed raw matter and rations of all livestock would be beneficial to investigate in terms of digestive system parameters and global warming, further in vitro and in vivo studies.